The relationship between frailty syndrome and quality of life in patients with hypertension: a multidimensional analysis - Bartosz Uchmanowicz; Anna Chudiak; Robbert Gobbens; Grzegorz Kubielas; Piotr Godek; Stanisław Surma; Dorota Bednarska-Chabowska; Izabella Uchmanowicz; Michał Czapla (BMC Geriatrics)
Abstract Background Hypertension is a common condition among the elderly and is frequently accompanied by frailty syndrome (FS). The coexistence of hypertension and FS poses significant challenges in patient management and negatively impacts the quality of life (QoL). This study aimed to analyze the relationship between FS and QoL in elderly patients with suspected hypertension. Methods A cross-sectional study was conducted involving 201 patients aged 65 years or older, referred to a Hypertension Clinic for diagnostic evaluation. Frailty was assessed using the Tilburg Frailty Indicator (TFI), and QoL was evaluated with the World Health Organization Quality of Life Instrument (WHOQOL-BREF). Sociodemographic and clinical data were collected, and statistical analyses were performed to identify correlations between FS and QoL. Results The study found that 79.60% of the patients were identified as frail (TFI ≥ 5). FS was significantly negatively correlated with all domains of QoL, including physical health (r = -0.634, p < 0.001), psychological health (r = -0.675, p < 0.001), social relationships (r = -0.528, p < 0.001), and environmental factors (r = -0.626, p < 0.001). Multivariate analysis revealed that physical (β = -0.091, p < 0.001) and psychological components of FS (β = -0.128, p = 0.016), as well as age (β = -0.022, p = 0.004), were significant predictors of lower QoL scores. Loneliness (β = -0.235, p = 0.049) was also a significant predictor of lower QoL. Conclusions The study demonstrated a strong association between FS and reduced QoL in elderly hypertensive patients, emphasizing the need for comprehensive assessments and personalized management strategies. Routine evaluation of frailty and the implementation of targeted interventions aimed at improving physical, psychological, and social well-being could substantially enhance QoL in this vulnerable population. Clinical trial number Not applicable.